PLANNING SCHEDULING OF GRADE SEPARATOR - R, Srikanth; R, Manjunath K. (International Journal of Students' Research in Technology & Management, 2015)
Planning, scheduling plays a vital role in improving the prospects of successful implementation of infrastructure projects. Project planning involves defining and coordinating activities and work tasks, preparing work schedules, assigning and allocating resources to competing activities and developing an acceptable budget. The scheduling is just one of the tools will be used to manage activities and duration.. The scope of this work is to Consistent view of project status and issues, is to ensure that the project is completed within the allocated and approved budget; Work Break Down structure will be prepared, duration and predecessors for each activity will be assigned, Critical Path will be determined, Resource analyzing and leveling will be done for entire,. Estimating is to assign resources to each activity in the activity list. Total duration and cost will come to know by using Microsoft Project. Based on prediction of future traffic at junction on chord road the grade separator is been projected. Accordingly the planning scheduling of grade separator at junction on chord road is been prepared. An effective planning, scheduling will help in emerging problems and taking time correctively action.